2002
DOI: 10.1111/1467-9566.00320
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer: embodied experience and perceptions of masculinity

Abstract: While some argue that gender differences, which refer to the social classification into 'masculine' and 'feminine', have their source in 'culture', others argue there is no need to have an absolute dichotomy between culture and nature, or between constructionist and anti-constructionist epistemologies. Although there has been much theorising about the body, until recently little attention has been paid to empirical evidence. This paper looks at the way in which prostate cancer and its treatment affects men's b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
265
1
10

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(286 citation statements)
references
References 46 publications
(35 reference statements)
10
265
1
10
Order By: Relevance
“…Patients have reported particular difficulties in the domains of self image, masculinities [15][16][17] and sexuality [18,19] which appear to relate to losses consequent on treatments for prostate cancer. Radical curative treatments can result in nerve or tissue damage, either eradicating erections or taking up to two years for partial erections to be recovered [20] and hormonal treatments can result in side effects that might be experienced as challenging to masculinity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Patients have reported particular difficulties in the domains of self image, masculinities [15][16][17] and sexuality [18,19] which appear to relate to losses consequent on treatments for prostate cancer. Radical curative treatments can result in nerve or tissue damage, either eradicating erections or taking up to two years for partial erections to be recovered [20] and hormonal treatments can result in side effects that might be experienced as challenging to masculinity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This reflects broader ignorance of the everyday experiences of men and their changing sense of masculinity when disease affects their genital organs [12]. The existing evidence is mixed.…”
Section: Introductionmentioning
confidence: 99%
“…The existing evidence is mixed. Fergus et al [13] found that prostate cancer and its treatment pose a significant threat to masculine identity and has a negative effect on men's sense of masculinity while Chapple and Ziebland [12] reported no major effects. It seems plausible that men's masculine identity is likely to be challenged by the experience of having prostate cancer and, in particular, by the consequences of surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have examined the effects of prostate cancer treatment on masculinity have used qualitative research designs and have reported a great sense of shame and embarrassment expressed by men as a result of their inability to perform sexually. Their decreased sense of masculinity arises from their inability to meet the perceived socially expected roles of being a man (Chapple & Ziebland, 2002;Fergus et al, 2002;Oliffe, 2005). Masculinity and men's perception of their relationships with their partners were considered as the environmental characteristics and independent variables since they represent the social influences on QOL in men with prostate cancer.…”
Section: Environmental Characteristicsmentioning
confidence: 99%
“…Seeking medical help is viewed by men as a form of weakness, and they reportedly preferred to deal with their symptoms and learn to live with them (Solomon, Greenberg, & Psyszczynski, 1991). This reluctance in seeking medical attention is especially true when symptoms are considered to be embarrassing and shameful such as urinary incontinence and sexual dysfunction (Chapple & Ziebland, 2002;Gray et al, 2002).…”
Section: Masculinity and Health Behaviorsmentioning
confidence: 99%